Manners and customs of Bible lands - Wight, Fred (Billy Graham Evangelistic Association, 1994)
The Bible written by Orientals. It is easy for Occidentals to overlook the fact that the Scriptures had their origin in the East, and that each one of the writers was actually an Oriental. Since this is so, in a very real sense the Bible may be said to be an Oriental Book. But many are quite apt to read into the Scriptures Western manners and customs, instead of interpreting them from the Eastern point of view.